Post-Partum Depression, Personality, and Cognitive-Emotional Factors: A Longitudinal Study on Spanish Pregnant Women. Issue 1 (2nd January 2016) - Peñacoba-Puente, Cecilia; Marín-Morales, Dolores; Carmona-Monge, Francisco Javier; Velasco Furlong, Lilian
Abstract : In this study, our purpose was to examine whether personality and cognitive factors could be related to post-partum depression (PPD), mediated by anxiety, in Spanish women. Women were evaluated for personality and cognitive factors after the first trimester, for anxiety in the third trimester, and for PPD 4 months after childbirth. A structural equation model revealed that personality and cognitive factors were associated with anxiety and PPD as predictors. Neuroticism and extroversion proved to be the most relevant factors. Conscientiousness was associated with pregnancy anxiety. Pregnancy anxiety appeared as an independent predictor of PPD. The model presented here includes personality and cognitive and emotional factors as predictors of PPD. Comprehensive care for pregnant women should contemplate assessment and intervention on all these aspects. Special focus should be on cognitive factors and emotional regulation strategies, so as to minimize the risk of later development of emotional disorders during puerperal phases.